Fujian – Penghu – Taiwan: Frühe Kontakte, nach Texten zusammengefaßt ( (ca. 200-1450 n. Chr.) - Ptak, Roderich (Abhandlungen für die Kunde des Morgenlandes, 2015)
Archaeologists have shown that Taiwan and the Penghu Islands had early contact with mainland China and other areas. However, this is about corresponding evidence in old written sources (approx. Han to early Ming period), which are presented in a critical overall view, mostly in chronological order. Much evidence remains controversial to this day, such as certain toponyms, but all in all they suggest that Penghu and Taiwan were primarily noticed in Fujian, and sometimes even played a certain role in the mainland's politico-military calculations - long before their arrival the first Europeans in the Far East and the beginning of "globalization". In short, the gaze wanders from the mainland to the island region. At the same time, Taiwan is embedded in larger maritime contexts: as an island that lay between the exchange zones of the East and South China Seas. Very important in this context is the development of traditional sea routes, especially the so-called east route from Fujian via Penghu towards Luzon, the Sulu zone and even further south. Overall, the presentation is designed as an introduction that appeals not only to historians but also to students .